Reseña de: Lozano-Vásquez, A. (Comp.). (2012). Platón y la irracionalidad. Bogotá: Ediciones Uniandes. ISBN : 978-958-695-830-1. Número de páginas: 256. - Flórez Flórez, Alfonso; Pontificia Universidad Javeriana (2015)
null